Effective Hamiltonian approach to the exact dynamics of open system by complex discretization approximation for environment - Cui, H. T.; Yan, Y. A.; Qin, M.; Yi, X. X. (APL quantum, 2025)
The discretization approximation method commonly used to simulate the dynamics of quantum systems coupled to the environment in continuum often suffers from the periodically partial recovery of the initial state because of the effect of finite dimension, dubbed the recurrence. To address this issue, we propose a generalization of the discretization approximation method into the complex frequency space based on complex Gauss quadratures. An effective Hamiltonian can be established by this way, which is non-Hermitian and demonstrates the complex energy modes with a negative imaginary part, describing the dissipation of the system. This method is applied to examine the dynamics in two exactly solvable models, the dephasing model and the single-excitation dissipative dynamics in the Aubry–André–Harper model. By comparison with the exact numerics and analytical results, it is found that our approach not only significantly reduces the effect of recurrence and improves the effectiveness of calculation but also provides a unique perspective into the dynamics of open systems from the point of complex energy levels. Furthermore, we establish a simple relationship between the parameters in computation and the effectiveness of simulation by analyzing the computational error.